Ocular toxicity of systemic anticancer chemotherapy - Omoti AE; Ooti CE (Centro de Investigaciones y Publicaciones Farmaceuticas, 2006)
The increased use of chemotherapeutic agents has resulted in longer cancer patient survival. Consequently the ophthalmologist is seeing more patients with adverse ocular side effects secondary to these antineoplastic agents. Ocular toxicity induced by cancer chemotherapy includes a broad spectrum of disorders, reflecting the unique anatomical, physiological and biochemical features of the eye. Understanding the ocular side effects will assist the ophthalmologist and oncologist to recognize them early and intervene before blindness occurs. Anticipation of various treatment-related toxicities may also provide the opportunity for pharmacists to develop intervention strategies that could minimize or eliminate an expected side effect. The ophthalmologist should examine patients on anticancer therapy at baseline and three monthly thereafter. The various ocular side effects of anticancer chemotherapeutic agents, tamoxifen, and interferon on the adnexia, anterior segment, posterior segment and neuro-ophthalmic structures were reviewed.